Stability Analysis of Mine Opening at Mine Decline by 3 Dimensional Finite Element Method - Arfan Dermawan Ikhsan, Muh
In stability assessment of underground opening, numerical modeling with finite element method (FEM) is needed. Stability assessment are also carried out at the stage of construct the work face before excavation the underground opening. In this study, 2D analysis was also conducted to compare the results of 3D analysis. The model developed for 3D FEM analysis is based on geometrical and geotechnical characteristics data as an input data's to be calculated based on FEM analysis. Geometrical data consist of topography, lithology domain, and mine plan design while the geotechnical characteristics of each lithology data obtained from rock mass classification data and laboratory test results. Numerical modeling is carried out considering the conditions of the external geometry boundary, strain conditions, loading condition, and mesh element discritization. Overall the stability of the underground mine opening is in a stable condition, which is in the range of the strength factor values arround 3 - 99 and stability with seismic effect that simulated in dry condition also in a stable condition with range of the strength factor values arround 1.5 - 97. Based on the results and analysis of the 3D FEM model, it was found that the topographic conditions, material load above the underground opening and gradient of mine decline affect the value of the material strength factor in the opening hole. The condition of the saturation level of the slope above the undergound opening and the effect of groundwater also affects the value of the material strength factor in the opening hole.